Arsenic removal from water using magnetic nanoparticles obtained by accvd (2013)
The development of magnetic nanoparticles by ACCVD is a powerful technique to synthesize material with high purity. The size and composition of magnetic nanoparticles was tailored, by variation of the flow ratio Ar-Air and furnace temperature. Different types of nanoparticles were obtained from metallic Fe until Fe2O3. The size of magnetic nanoparticles was between 195 nm and 272 nm. The synthesis temperature was between 440 and 590 oC. The nanoparticles were collected by using an impactor plate at 120 oC. The obtained materials were characterized by high resolution electron microscopy, X-ray diffraction and ICP-MS. These particles were used to remove arsenic from contaminated water. The magnetic nanoparticles showed a high capacity to adsorb arsenic. The initial concentration of arsenic in water was 20 ppbs and after remotion with hematite the arsenic disappeared from solution. To remove arsenic from solution the ultrasonic method was used to mix the magnetic nanoparticles with arsenic and subsequent precipitation with super magnets.